Self-efficacy in the adoption and use of online commercial databases : a case study of 4th year level bachelor of information studies degree students, University of Limpopo, South Africa - Moraka, Thereza (My University, 2020)
OCD training outcomes were meant to produce students with high self-efficacy levels in using search tools and techniques and ultimately adopting and use of OCDs in their academic work. The researcher distributed a questionnaire to sixty-six (66) 4th year level BIS degree students at the University of Limpopo. The study employed mixed-method to collect data and analysed data using Social Statistical Package Software and content analysis. Findings from content analysis show that post OCD training majority of the respondents indicated enhanced self-efficacy, but content analysis show continued use of free online databases among those with high and low self-efficacy levels. The adoption and use of OCDs among those who failed to grasp the use of certain search tools and strategies could be reliance on gross searching strategies. Overall OCD training was beneficial to the majority of respondents
Thesis (M. Information Studies) -- University of Limpopo, 2020
Keywords: Self-efficacy; Online commercial databases; Free online databases; Online commercial database training; Information storage and retrieval systems -- Databases; Online databases; Databases; Electronic information resource literacy